Psychometric Indicators and Adaptation of the Ukrainian Version of the Social Networking Addiction Scale (M.G. Shahnawaz, U. Rehman Social Networking Addiction Scale) - Pavlo Sevostianov; Svitlana Yanovskaya; Rimma Turenko; Darіa Pyvovar (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Психологія)
The article presents the results of adapting the Social Networking Addiction Scale (M.G. Shahnawaz, U. Rehman) for use in Ukrainian samples of subjects. It is defined that social networking sites are virtual communities, where participants create individual public profiles to communicate with friends, meet people, and show their life stories. It is shown that immersion in the online environment can lead to addiction to social networks, which requires studying. The Ukrainian version of the questionnaire included 11 items that allow measuring social network addiction by such factors as “Salience”, “Withdrawal” and “Conflict”. The sample consisted of 382 individuals (210 women and 172 men) aged 18 to 64 years. The survey was conducted using Google Forms with informed consent from the subjects to participate and process the results. The validation included checking the factor structure of the original questionnaire using confirmatory factor analysis (with the DWLS estimator); determining the internal consistency of the methodology factors using Cronbach’s α coefficient; checking the construct validity of the questionnaire (connection with the Internet Addiction Test by K. Young and the Addictive Behavior Propensity Scale); and determining its retest reliability using Spearman's correlation analysis. The indicators of social media addiction were compared, taking into account gender; their relationship with the age of the subjects was also analyzed. The results of the adaptation proved the suitability of the questionnaire for use on Ukrainian samples of subjects.